Somatic copy number variant mutations in alpha-synuclein and genome-wide in brains of synucleinopathy cases. Issue 6 (27th May 2022) - Perez-Rodriguez, Diego; Kayla, Maria; Leija-Salazar, Melissa; Lashley, Tammaryn; Warner, Thomas; Gentleman, Steve; Schapira, Anthony; Holton, Janice; Jaunmuktane, Zane; Proukakis, Christos
Abstract : Synucleinopathies are mostly sporadic neurodegenerative disorders, and include Parkinson's disease (PD), and multiple system atrophy (MSA). Inherited copy number variants (CNVs) of SNCA (α-synuclein) are rare causes of familial disease. There is increasing evidence for somatic mutations in the human brain, and we have hypothesized a role for these in synucleinopathies. We further investigated somatic CNVs in brains from synucleinopathy cases, using Fluorescent in-situ Hybri- disation for SNCA gains, and single-cell whole genome sequencing for the first time in a synucleinopathy. In the cingulate cortex, mosaicism for SNCA gains was higher in MSA and PD than controls in neurons (> 2% in both diseases), and for MSA also in non-neurons. In MSA substantia nigra (SN), we noted SNCA gains in > 3% of cells. Cells with CNVs were more likely to have α-synuclein inclusions, in a pattern corresponding to cell categories mostly relevant to the disease: dopaminergic neurons in Lewy-body cases, and other cells in striatonigral degeneration-dominant MSA (MSA-SND). Higher SNCA CNV mosaicism in typical MSA-SND SN non-dopaminergic cells may correlate with younger onset, and in PD cingulate neurons with younger death. Whole genome sequencing of 169 single cells from two MSA cases showed somatic CNVs in 30%. Neurons had gains and losses, and other cells almost exclusively gains. We propose that somatic SNCA CNVs contribute to the aetiology and pathogenesis of synucleinopathies, and that genome-wide somatic CNVs merit further study c.proukakis@ucl.ac.uk